Dyadic Goal Setting and Role Stress: A Field Study - Quick, James Campbell (Academy of Management Journal, 1979)
A field study was conducted over a 14 month period to examine goal setting as a dyadic, role making process between 46 managerial and staff employees (subordinates) and 15 officers and directors (supervisors) in an insurance company. Significant improvements in the goal behaviors and significant declines in stress were found following training.